Danggui Niantong granules in the treatment of rheumatoid arthritis - a mechanistic approach using ceRNA networks - Cai, Yisi; Song, Yanyan; Zeng, Xiaoling; Liu, Gang; Yuan, Lixia (Frontiers in Pharmacology, 2026)
ContextDanggui Niantong granules (DGNTG), a traditional Chinese medicine, serve as an effective therapeutic agent for the treatment of rheumatoid arthritis (RA). However, the comprehensive molecular mechanisms of DGNTG in RA remain unclear. Increasing evidence highlights the significant role of competing endogenous RNAs (ceRNA) in diagnosing and treating various diseases.ObjectiveThe study aims to explore the molecular mechanism of DGNTG in the treatment of RA through the ceRNA network.Materials and methodsThe MH7A cells were divided into control group and DGNTG group (2 and 4 mg/mL).The proliferation, migration and invasion ability of MH7A were accessed using MTT assay, cloning formation, wound-healing assay transwell assay and Western blotting. Subsequently, ceRNA microarray analyses were performed and a circRNA-miRNA-mRNA ternary transcription network was established. The data were validated through qPCR.ResultsDGNTG inhibited proliferation, suppressed migration and invasion in MH7A (P < 0.05, 0.01 or  0.001), with the most pronounced effects observed in the DGNTG (4 mg/mL) group. Subsequently, we identified 301 differentially expressed mRNAs and 507 differentially expressed circRNAs (FC ≤ 0.5 or ≥2, P < 0.05). Bioinformatics analyses indicated that DGNTG may exert therapeutic effects through multiple pathways. Furthermore, we constructed a circRNA-miRNA-mRNA network and conducted additional bioinformatics analysis on this network. In addition, we developed a representative ceRNA network and analyzed the correlations among its components.Discussion and conclusionsThis study presents evidence that DGNTG exerts anti-RA effects through the inhibition of synoviocyte proliferation, migration and invasion. Additionally, It provided a valuable resource for elucidating the mechanism of action of DGNTG by constructing a competing endogenous RNA network based on transcriptomic data obtained from DGNTG-treated MH7A cells.